10.61533 PENYUSUNAN STRATEGI UNTUK MENINGKATKAN BRAND AWARENESS PADA PT PRIORITAS INTI SEJAHTERA MENGGUNAKAN ANALISIS SWOT - Tohady, Enjellika; Shinta Lestari, Deara; Ruben Manullang, Rizal (STIE IBEK Pangkalpinang, 2024)
Seeks to improve brand recognition among the company's B2B partners to support future market expansion. This qualitative descriptive research, conducted from February to June 2024, comprises 89 pages, excluding appendices. Utilizing the 7P Marketing Mix framework, the research assesses the company’s internal and external environments, resulting in Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) scores of 5.53403537 and 6.2229091116, respectively. The analysis positions the company in Quadrant 1, indicative of a Growth Oriented Strategy. This strategy recommends an assertive implementation of the 7P Marketing Mix components. The SO strategy harnesses strengths and opportunities, the ST strategy employs strengths to counter threats, the WO strategy exploits opportunities to address weaknesses, and the WT strategy aims to mitigate weaknesses and avert threats. The findings indicate that PT Prioritas Inti Sejahtera’s brand awareness is relatively low, attributed to its recent market entry. This is evidenced by the lower number of application downloads and active users compared to competitors. Therefore, a Growth Oriented Strategy is proposed to increase brand awareness.